Identifications and typifications of Ficus pubigera var. maliformis and related names - Zhang, Zhen; Liao, Shuai; Li, Hong-Qing; Zhang, De-Shun (Phytotaxa, 2020)
In Ficus subsect. Plagiostigma, the identities of F. pubigera var. maliformis and some other related names are confusing presently, which hinders their precise application. Based on extensive examinations of related specimens, the lectotype of F. foveolata var. maliformis is designated here. F. pubigera var. maliformis is proved to be misapplied so far in most floras and herbaria. Furthermore, F. yunnanensis is treated as a new synonym of F. pubigera var. maliformis, and F. howii is reinstated to be a separate species, which had been wrongly identified as F. pubigera var. maliformis.